Oncolytic virotherapy armed with an engineered interfering lncRNA exhibits antitumor activity by blocking the epithelial mesenchymal transition in triple-negative breast cancer. (1st June 2020) - Ang, Lin; Guo, Lingli; Wang, Jin; Huang, Jin; Lou, Xiaoli; Zhao, Min
Abstract: Triple-negative breast cancer (TNBC) has special characteristics of significant aggressiveness, and strong potential for metastasis and recurrence; currently there are no targeted drugs for TNBC. Abnormal activation of epithelial-mesenchymal transition (EMT) plays an important role in these malignant behaviors of TNBC. In the crosstalk among the multiple EMT-associated signaling pathways, many miRNAs participate in regulating pathway activity, where they act as "traffic lights" at the intersection of these pathways. In this study, we used miRNA microarray technology to detect differentially expressed miRNAs related to EMT in TNBC, and we identified and verified 9 highly expressed oncogenic miRNAs (OncomiRs). High expression of these OncomiRs in clinical breast cancer tissues affected the prognosis of patients, and inhibition of their expression blocked EMT in TNBC cell lines and suppressed cancer cell proliferation and migration. We constructed an oncolytic adenovirus (AdSVP-lncRNAi9) armed with an artificially-designed interfering lncRNA (lncRNAi9), which exhibited an activity to block EMT in TNBC cells by disrupting the functions of multiple OncomiRs; the efficacy of such a treatment for TNBC was demonstrated in cytology and animal experiments. This research provides a new candidate oncolytic virotherapy for treating highly malignant refractory TNBC. Highlights: A group of oncogenic miRNAs (OncomiRs) were found to be overexpressed in TNBC. These OncomiRs were demonstrated to be associated with cancer cell EMT. Oncolytic virotherapy armed with interfering lncRNA was designed. The therapeutic strategy can inhibit OncomiRs and block EMT in TNBC.